1981
DOI: 10.2135/cropsci1981.0011183x002100010031x
|View full text |Cite
|
Sign up to set email alerts
|

Callus Initiation and Plant Regeneration from Triticale Embryos1

Abstract: This study was conduced to determine optimal concentrations of sucrose and combinations of growth regulators required for callus initiation and plant regeneration from immature embryos of 'Councill' and other triticales (X Triticosecale Wittmack) and to make histological observations of triticale callus during differentiation and organogenesis. Immature triticale embryos were cultured on a basal medium containing the salts of Murashige and Skoog and vitamins plus selected concentrations of sucrose and differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Chin and Scott (1977) obtained satisfactory shoot induction rates from embryo callus by applying a combination of NAA (1 mg/1) and kinetin (5 mg/1). However, as indicated by the results obtained in the present study (experiments 1 and 2) and by the data reported by Sharma et al (1981) (for Triticale embryos) and Kintzios et al (1996) (for T. aestivum and T. durum embryos), this combination of growth regulators might have been less appropriate for shoot induction than the application of NAA alone.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Chin and Scott (1977) obtained satisfactory shoot induction rates from embryo callus by applying a combination of NAA (1 mg/1) and kinetin (5 mg/1). However, as indicated by the results obtained in the present study (experiments 1 and 2) and by the data reported by Sharma et al (1981) (for Triticale embryos) and Kintzios et al (1996) (for T. aestivum and T. durum embryos), this combination of growth regulators might have been less appropriate for shoot induction than the application of NAA alone.…”
Section: Discussionsupporting
confidence: 60%
“…1 Auxin applied at high concentrations during the induction and proliferation phases and carried over with calli subcultured for root and shoot induction, as previously reported for 2,4-D in Triticale (Sharma et al 1981) and wheat (Kintzios et al 1996), or; 2 The increased root induction at high auxin and NaCl concentrations. This competition between root induction and shoot induction was clearly observed in all three experiments: when root formation preceded shoot induction and roots were induced at high percentages (experiments 1 and 2) low shoot induction rates were observed.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Cytokinin-supplemented media did not induce sustained growth of callus from embryos ( Table 1). The usefulness of 2,4-D as an effective auxin for caUus initiation and growth has been demonstrated for wheat [4,11], maize [5,6], barley [1] and triticale [13]. 2,4,5-T has been found to be very effective in caUus cultures of wheat [2].…”
Section: Initiation Of Callus Cultures J)'om Immature Embryosmentioning
confidence: 99%
“…In vitro techniques to induce direct somatic embryogenesis, secondary embryogenesis, and plant regeneration from cereals require a specific sequence of defined media, hormonal composition, and controlled growth conditions. Application of 2,4-D as an effective auxin for direct somatic embryogenesis, embryogenic callus initiation and growth have been demonstrated in triticale like in other cereals (Sharma et al 1981). Besides 2, 4-D, various other growth regulators -2, 4, 5-T and 2, 4, 5-CI 3 POP-are also shown to be suitable for initiation and maintenance of callus cultures from immature embryos in triticale though at a lesser extent (Eapen and Rao 1982).…”
Section: Immature Embryo and Scutellum Culturementioning
confidence: 99%